Post-polymerization modifiable aromatic (co)poly(ether sulfone)s possessing pendant norbornenyl groups based upon a new bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (European Polymer Journal, 2022)
A new bisphenol possessing pendant norbornenyl group viz., 4, 4 `-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was synthesized by a single-step base-catalyzed condensation reaction of 5-norbor-nene-2-carboxaldehyde with guaiacol. NMR spectral data indicated formation of BPA-NB comprising of isomeric components. A series of (co)poly(ether sulfone)s possessing pendant norbornenyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar ratio of BPA-NB and bisphenol-A (BPA) with bis(4-fluorophenyl) sulfone. Inherent viscosity values and number average molecular weights of (co)poly (ether sulfone)s were in the range 0.67-1.01 dL/g and 75,400-1,16,300 g/mol, respectively indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)poly(ether sulfone)s. (Co)poly(ether sulfone)s were characterized using FT-IR, H-1 NMR and C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The formation of random copoly(ether sulfone)s was demonstrated by( 13)C NMR analysis. The incorporation of BPA-NB into (co)poly(ether sulfone)s resulted into improvement in Tg values. BPA-NB-based (co)poly(ether sulfone)s offered possibilities for post -modifications involving either methoxyl or norbornenyl groups. A representative copoly(ether sulfone) (PSU-NB-2) possessing pendant norbornenyl groups was chemically modified via thiol-ene reaction with three representative thiol compounds, namely, 1-dodecanethiol, 2-furanmethanethiol and 2-mercaptoethanol to yield corresponding post-modified polymers in a quantitative manner. Additionally, it was demonstrated that copoly (ether sulfone) possessing pendant norbornenyl groups could be used to form insoluble cross-linked gel in the presence of a multifunctional thiol cross-linker.
Keywords: (Co)poly(ether sulfone)s; bisphenol; Cross -linking; Pendant norbornenyl groups; Thiol-ene reaction